Effectiveness of dinoprostone vaginal pessary in induction of labour at term - Pitale, Devdatt L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Induction of labour is a very common obstetric procedure worldwide. The ultimate goal of induction of labour is to achieve a successful vaginal delivery. Dinoprostone is a Prostaglandin (PGE2) which acts on the collagen structural network of the cervix and makes it favourable, thus increasing the chances of a successful of a vaginal delivery. This study emphasizes on the importance of having a proper induction protocol in place and at the same time judicious use of the agents for induction of labour. This will help to reduce the maternal anxiety and stress associated with the induction of labour. The present study was undertaken to assess the effectiveness of dinoprostone vaginal pessary in induction of labour at term. Methods: Twenty patients with unfavorable cervix at term were studied for the effectiveness of Dinoprostone vaginal pessary in induction of labor. Results: Among the twenty patients 17 (85%) delivered vaginally within 18 hrs and 3 (15%) were in the active phase of labour. No untoward event was observed in any of the cases with a favorable neonatal outcome in all the cases. Conclusions: Present study shows that Dinoprostone vaginal pessary is a highly effective method of induction of labor at term in properly selected cases. It reduces consistently the number of internal examinations and thus reducing the risk of ascending infections adding to it's safety along with reduced maternal anxiety associated with induction of labour.